Big Data in Tourism and Hospitality Industry: Predictive Analytics of Hotel Room Trends - Singgalen, Yerik Afrianto (Lasigo Akademia Indonesia, 2025)
This study investigates predictive analytics applications in the hospitality sector, specifically employing the XGBoost algorithm to predict room selection patterns based on guest data. Analysis of 900 booking records revealed that three variables—